Thiamine accumulation and thiamine triphosphate decline occur in parallel with ATP exhaustion during postmortem aging of pork muscles. (March 2018) - Muroya, S.; Oe, M.; Ojima, K.
Abstract: We aimed to clarify the mechanisms affecting postmortem thiamine and its phosphoester contents in major edible pork muscles, namely the longissimus lumborum (LL) in addition to vastus intermedius (VI). Metabolomic analysis by capillary electrophoresis-time of flight mass spectrometry revealed that the level of thiamine triphosphate (ThTP), approximately 1.8-fold higher in LL than in VI muscle at 0 h postmortem, declined in the first 24 hrs, resulting in an undetectable level at 168 h postmortem in both muscles. In contrast, the thiamine content in both muscles increased after 24 h postmortem during the aging process. The thiamine accumulation and ThTP decline progressed in parallel with a drastic reduction of the ATP level. The intermuscular differences in pH at 24 h and in expression of thiamine transporter and thiamine pyrophosphokinase might result in delayed thiamine generation in LL. These results suggest that postmortem ATP exhaustion forced ThTP hydrolysis and further depyrophosphorylation of thiamine diphosphate in the porcine muscles, which resulted in thiamine accumulation. Highlights: Levels of ThTP and ATP decline in parallel during postmortem pig longissimus muscle. Thiamine level in pig longissimus and vastus intermedius increases in the duration. Changes in thiamine and its phosphate levels were different between the muscles. Expressions of genes related to thiamine metabolism differ between the two muscles.